Outplanting performance of the Bornean tropical indigenous species Shorea macrophylla (de Vriese) P.S. Ashton in relation to seedling age - Perumal, Mugunthan; Wasli, Mohd Effendi; Ho, Soo Ying (Hindawi, 2021)
Planting high-quality seedlings with desirable growth attributes are associated with successful survival and growth performance following outplanting. Considering that most tree species from the Dipterocarpaceae family are on the IUCN Red List of Threatened Species, proper conservation of such species is necessary. Very little is known with no clear consensus regarding whether increasing the seedling production period enhances outplanting survival and growth potential of tropical dipterocarp species planted under enrichment planting in Malaysia. In this study, one potential Bornean tropical indigenous species, Shorea macrophylla (de Vriese) P.S. Ashton, was produced in the Universiti Malaysia Sarawak nursery and outplanted at Sampadi Forest Reserve, Sarawak. Different nursery production periods (3, 6, 9, and 24 months) were tested for the species at the time of planting as well as for the subsequent growth performance after 12, 24, and 42 months of outplanting. The findings revealed that older (9- and 24-month-old) S. macrophylla seedlings were morphologically larger from younger (3- and 6-month-old) seedlings. Nonetheless, the overall pooled mean survival rates declined from 61.7 to 44.6% after 12, 24, and 42 months of outplanting. For the 42-month period, the survival rate for the 9-month-old seedlings was significantly higher than that for the 3-, 6-, and 24-month-old seedlings. Notwithstanding, the relative growth rate of the stem diameter was higher for the 3- and 9-month-old seedlings than for the 6- and 24-month-old seedlings after 42 months of outplanting. Thus, maintaining plant material from the seedlings produced at 3, 6, and 9 months of age would be beneficial for the initiation of transplantation in restoration programmes in Sarawak. The 24-month-old seedlings will also be useful, especially during irregular flowering and unpredictable fruiting intervals. A further experimental study on other environmental factors that could influence the outplanting performance of the seedlings in the tropical forest restoration area of Sarawak, Malaysia, is necessary.